The synthesis of a high-quality biodiesel product derived from Krabok (Irvingia Malayana) seed oil as a new raw material of Thailand. (15th January 2022) - Roschat, Wuttichai; Phewphong, Sunti; Pholsupho, Phongsakorn; Namwongsa, Krittiyanee; Wongka, Pimwipha; Moonsin, Preecha; Yoosuk, Boonyawan; Promarak, Vinich
Graphical abstract: Highlights: Krabok ( Irvingia Malayana ) seed oil as a new raw material for biodiesel production. Krabok seed flesh gave the extract oil content up to 63.58 wt%. Krabok seed oil-based biodiesel showed similar properties to high-speed petroleum diesel oil. Abstract: The production of high-quality biodiesel product from Krabok ( Irvingia Malayana ) seed oil, new high efficiency, and high potential raw material, was studied using liquid biofuel energy in Thailand. The seed flesh of Krabok was extracted with hexane as a solvent by several techniques to compare the efficiency of each extraction method. The optimal technique for extracting the oil from the Krabok seed flesh was the Soxhlet extraction method which could extract oil content up to 63.58 wt%. The major fatty acid compositions of the obtained Krabok seed flesh oil were lauric acid (C12:0 ) and myristic acid (C14:0 ) as around 52 and 35 wt%, respectively. Additionally, the results also found that the extracted Krabok seed flesh oil was obtained greater than 95 wt% of the saturated fatty acid compound. The synthesis of a high-quality biodiesel product from Krabok seed flesh oil was performed via a one-step transesterification process catalyzed by a CaO catalyst. The obtained Krabok seed flesh oil biodiesel product was within both the ASTM-D6751 and EN-14214 standards for liquid bio-auto fuels, and it has properties that were very close to high-speed petroleum diesel oil. Consequently, the Krabok seed flesh oil was one of the exciting sources of raw materials in terms of high efficiency, quality, and potentiality in the production of biodiesel products.